Correctional officer recruits’ navigation of overwhelm: Internal and external strategies - Konyk, Katy (International journal of law, crime and justice, 2025)
Internationally, little is known of how correctional officer recruits (CORs), those beginning their careers as federal COs, navigate states of overwhelm (i.e., moments of acute stress) and whether their responses to overwhelm could be adaptive to the carceral environment. In this study, we analyze qualitative interviews with 27 Canadian CORs (18 male, 8 female) on navigating overwhelm to understand their preemployment strategies for responding to acute stress. Our grounded theory analysis reveals that CORs engage in both externally focused (i.e., stressor resolution) and internally focused (i.e., emotion regulation) coping strategies to navigate overwhelm. Additionally, CORs seek out relational support and identify how overwhelm can be an opportunity to grow and learn new strategies. We discuss how CORs’ reports of employing both problem-focused and emotion-focused coping strategies can shape how the organization supports CORs and COs in maintaining and developing new coping skills for overwhelm, specifically by creating conditions for regulatory flexibility and fostering strong relationships.